2023
DOI: 10.1089/imr.2022.0079
|View full text |Cite
|
Sign up to set email alerts
|

Participant Perspectives on Community Qigong for People with Multiple Sclerosis

Abstract: Introduction: Multiple sclerosis (MS) is a progressive neurodegenerative disorder affecting motor and nonmotor function including physical and cognitive decline, fatigue, anxiety, and depression. Qigong is a mind–body self-care practice with the potential to address MS symptoms. Publicly available community qigong classes may provide opportunities for people with MS to access qigong, but little is known about the risks and benefits. A mixed methods study of community qigong was conducted for peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Mind-body therapies (MBTs), including tai chi and qigong as well as hypnosis, imagery and yoga were found to be effective in addressing a myriad of psychosocial and physical symptoms and biomarkers as well as immune function for people suffering from cancer [91]. Patients having multiple sclerosis also benefitted by incorporating qigong exercises into their medical regimen [92]. A study of the effects of exercise on sleep in perimenopausal; women found that various kinds of exercise, including yoga, walking, fitness qigong and aerobics all had a beneficial effect, but qigong was the most effective technique when practiced for 10-12 weeks with a frequency of more than 3 times a week for a duration of 30-60 minutes [93].…”
Section: Recent Studiesmentioning
confidence: 99%
“…Mind-body therapies (MBTs), including tai chi and qigong as well as hypnosis, imagery and yoga were found to be effective in addressing a myriad of psychosocial and physical symptoms and biomarkers as well as immune function for people suffering from cancer [91]. Patients having multiple sclerosis also benefitted by incorporating qigong exercises into their medical regimen [92]. A study of the effects of exercise on sleep in perimenopausal; women found that various kinds of exercise, including yoga, walking, fitness qigong and aerobics all had a beneficial effect, but qigong was the most effective technique when practiced for 10-12 weeks with a frequency of more than 3 times a week for a duration of 30-60 minutes [93].…”
Section: Recent Studiesmentioning
confidence: 99%